A Study of Illocutionary Acts Used by Poppy and Kate in â€œWild Childâ€ Movie - Ashfi Kadarol Qolbi; Wijayadi -; Farhan Noor (Tell : Teaching of English Language and Literature Journal, 2016)
The aim of this research is to investigate types of illocutionary acts used by main characters in Wild Child and the purpose of illocutionary acts. The researcher uses descriptive qualitative method since she describes the phenomena of illocutionary act used by Poppy and Kate. The researcher uses the script of Wild Child movie as the data source to be analyzed and the researcher took some internet references and books as the supporting data for analyzing and discovering the types of illocutionary acts in this movie. This research found four types of illocutionary acts. There are representative, directive, expressive, and commisive. This research did not found illocutionary acts of declarative. The most of utterance used by Poppy and Kate is directive utterance. The purpose of illocutionary acts is to get someone to do something.